Barriers to cancer pain management from the perspective of patients: A qualitative study - Samira Orujlu; Hadi Hassankhani; Azad Rahmani; Zohreh Sanaat; Abbas Dadashzadeh; Atefeh Allahbakhshian (Wiley, 2022)
Abstract Aim The aim of this study was to explore the barriers to effective pain management in Iranian people with cancer. Design A qualitative descriptive design was used. Methods This qualitative descriptive study was performed on 14 people with cancer. Data were collected using semi‐structured interviews and analysed by Graneheim and Lundman's content analysis method. Results Four main categories emerged in relation to barriers to pain management from the perspective of people with cancer. Categories included 1) accepting and enduring divine pain, 2) negative attitudes towards the effectiveness of analgesics, 3) patients' low knowledge of pain self‐management methods and 4) neglected pain management. Barriers to pain management are multidimensional in nature consisting of patients, healthcare providers and system components. Therefore, attempts should be focused on the education of patients and healthcare providers about pain management and eliminating the shortcomings of the healthcare system.